Family planning uptake and its associated factors among women of reproductive age in Uganda: An insight from the Uganda Demographic and Health Survey 2016. - Anthony Mark Ochen; Che Chi Primus (Public Library of Science (PLoS), 2023)
Despite the government efforts to reduce the high fertility levels and increase the uptake of family planning services in Uganda, family planning use was still low at 30% in 2020 which was the lowest in the East African region. This study was undertaken to determine the prevalence and factors associated with the uptake of family planning methods among women of reproductive age in Uganda. This community-based cross-sectional study utilized secondary data from the Uganda Demographic and Health Survey (UDHS) of 2016. The survey data was downloaded from the Measure Demographic Health Survey website after data use permission was granted. Data was collected from a representative sample of women of the reproductive age group (15-49 years) from all 15 regions in Uganda. A total of 19,088 eligible women were interviewed but interviews were completed with 18,506 women. Data analysis was performed using SPSS statistical software version 32.0 where univariable, bivariable, and multivariable analyses were conducted. The prevalence of family planning use was found to be 29.3% and that of modern contraceptive use was found to be 26.6%. Multivariable analysis showed higher odds of current family planning use among older women (40-44 years) (aOR = 2.09, 95% CI: 1.40-3.12); women who had attained the secondary level of education (aOR = 1.91, 95% CI: 1.32-2.76); those living in households with the highest wealth index (aOR = 1.87, 95% CI: 1.29-2.72); and awareness of the availability of family planning methods (aOR = 1.41, 95% CI: 1.17-1.72). In conclusion, the study suggests improving women's education attainment, socio-economic position, and awareness may help increase use in the population.